Quality Culture: Starting Point To Form Competitive Human Resources - Andika Prasetya Nugraha; Sarmini Sarmini; Sabri Sabri; Mulyadi Mulyadi; Andi Hidayatul Fadlilah (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2024)
The "Quality Culture" program at Nabilah Batam Islamic High School aims to develop competitive human resources through socialization and interactive discussions with students. The material presented covers the importance of quality culture, strong character development, and strategies to enhance competitiveness. Questionnaire results show increased motivation, self-confidence, understanding of quality culture, and students' readiness to improve competitiveness after participating in this program, with a Respondent Achievement Level (TCR) value of 57.65%. The main driving factors are strong commitment from the school, teacher support, and student enthusiasm. Meanwhile, the challenges include limited resources and diverse student backgrounds. The program produces outputs in the form of quality young people and social activities conducted by students. To enhance program effectiveness, strengthening school leadership commitment, implementing sustainable teacher development programs, and actively involving parents and the community are necessary. With these efforts, the school can build a stronger quality culture, improve education quality, and produce high-achieving and competitive graduates in both academic and non-academic fields. The collaboration between the school, teachers, students, and the community has been crucial in overcoming challenges and ensuring the program's success in preparing students to become competitive human resources and contribute positively to society.